Preparation and application of mixed molecule embedded near-layered organic hybrid vanadium oxide material
By introducing a mixed solvent of ethylene glycol and glycerol into the vanadium oxygen material, a near-layer organic hybrid vanadium oxygen material embedded in the mixed molecule is prepared, which solves the problem of irreversible phase change in the vanadium oxygen material during the cycle process, and realizes the High specific capacity, good rateability and long-term cycle stability.
Patent Information
- Application Number
- CN202411642418.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing vanadium oxygen materials have irreversible phase change during the circulation process, resulting in poor stability and cycling performance of the electrode materials.
By co-intercalating the vanadyl precursor with mixed molecules embedded in ethylene glycol and glycerol, a near-layer organic hybrid vanadium oxygen material was prepared by co-intercalating the vanadyloxy precursor with mixed molecules. The material forms a spherical structure of nanosheet stacking through solvothermal reaction and subsequent treatment, and has excellent electrochemical properties.
The high specific capacity, good rateability and long-term cycle stability of vanadium oxygen materials are achieved, and the irreversible phase change of metal ions in the frame is avoided.
Smart Images

Figure CN119447198A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a mixed molecule embedded near-layered organic hybrid vanadium oxide material, belonging to the technical field of zinc ion battery electrode materials. Background Art
[0002] Electrochemical energy storage systems are considered to be an important component of achieving dual carbon at this stage due to their green and efficient characteristics. Currently, widely used lithium-ion batteries are limited in large-scale production due to the increasing scarcity of lithium resources and the safety hazards caused by their own organic electrolytes. Therefore, green, safe and highly ionic conductive aqueous metal ion batteries (such as sodium, manganese, aluminum, zinc, etc.) are gaining more and more attention.
[0003] Among various electrode materials, vanadium oxides of vanadium-based positive electrodes have good structural stability and high theoretical capacity, so their application prospects in battery materials are very broad. Among them, vanadium elements are active in nature, have multiple valence states, are cheap, and have abundant reserves. Its compounds show strong metal ion storage capacity and have high theoretical specific capacity and discharge voltage platform as well as different crystal structures. Therefore, vanadium-based oxide materials have become the most promising electrode materials.
[0004] Traditional layered structural materials have the characteristics of weak van der Waals interactions between layers, and strong in-plane chemical bonds, which promote extension in the in-plane direction, providing an unobstructed channel for accommodating foreign ions, especially multivalent metal ions or hydrated ions with a larger radius. However, due to the strong electrostatic effect of metal ions in vanadium oxide materials, the cyclicity is limited, the electrode material will dissolve during the charge and discharge process, and long-term accumulation will cause the electrode material to change phase.
[0005] Currently reported optimization strategies for vanadium oxide materials include metal ion doping and water intercalation strategies. In addition, vanadium oxide is compounded with organic molecules such as polyaniline, ethylene glycol, and ethylenediamine to improve the electrochemical performance of electrode materials. However, it still faces the problem of irreversible phase changes during the embedding and extraction of metal ions in its framework. Summary of the invention
[0006] The purpose of the present invention is to provide the preparation and application of a mixed molecule embedded near-layered organic hybrid vanadium oxide material, which utilizes a mixed solvent of ethylene glycol and propylene glycol to co-intercalate a vanadium oxide precursor to construct a stable mixed molecule embedded near-layered organic hybrid vanadium oxide material; the mixed molecule embedded near-layered organic hybrid vanadium oxide material is used as a positive electrode material for an energy storage device (such as an aqueous zinc ion battery), and has excellent electrochemical properties, specifically showing excellent rate performance, high specific capacity, good reversibility and long-term cycle stability.
[0007] To achieve the above-mentioned purpose, the technical scheme of the present invention is implemented as follows: the preparation of a near-layered organic hybrid vanadium oxide material embedded with mixed molecules is characterized in that it comprises the following steps: 1) adding a vanadium oxide precursor material to a solution obtained by fully stirring an aqueous solution and an organic polyol mixed solvent in a volume ratio of 11 mL:6 mL, and mixing the solution and then fully stirring the solution again, the stirring temperature is room temperature, the time is 12 h~48 h, preferably 12 h, to obtain a mixed solution; 2) performing a solvothermal reaction of the mixed solution in a stainless steel reactor, the lining of the stainless steel reactor is preferably a polytetrafluoroethylene material, the temperature of the solvothermal reaction is 180 ℃~210 ℃, preferably 205 ℃; the insulation time is 24 h~48 h, preferably 36 h; 3) after the solvothermal reaction is completed and cooled naturally, taking out the reaction liquid, repeatedly washing the precipitate obtained by centrifugation with ethanol until impurities are removed, and drying in an oven, the drying temperature is 60 ℃~100 ℃, preferably 80 ℃; the time is 12 h~48 h, preferably 24 h, obtaining a near-layered organic hybrid vanadium oxide material in which the mixed molecules are embedded.
[0008] The organic polyol mixed solvent includes one or both of ethylene glycol and glycerol.
[0009] The vanadium oxide precursor material is vanadium oxide or vanadate, wherein the vanadium oxide includes commercial V2O5, and the vanadate includes NH4VO3.
[0010] The volume ratio of ethylene glycol to propylene glycol in the organic polyol mixed solvent is 1-4:2.
[0011] The molar mass ratio of the vanadium oxyhydroxide precursor material in the mixed solution is 0.1176 mol / L.
[0012] The mixed molecule embedded near-layered organic hybrid vanadium oxygen material contains vanadium, oxygen, carbon and hydrogen.
[0013] The near-layered organic hybrid vanadium oxide material in which the mixed molecules are embedded is a spherical structure of nanosheet stacking.
[0014] The application of the mixed molecule embedded near-layered organic hybrid vanadium oxide material in electrode materials of energy storage devices.
[0015] The energy storage device is preferably an aqueous zinc ion battery, and the electrode material is preferably a positive electrode material.
[0016] The electrode material of the energy storage device includes a near-layered organic hybrid vanadium oxide material embedded with mixed molecules, a conductive agent and a binder; the mass ratio of the near-layered organic hybrid vanadium oxide material embedded with mixed molecules, the conductive agent and the binder is 7:2:1; the conductive agent is carbon black Super-p, and the binder is polyvinylidene fluoride PVDF.
[0017] The positive effect of the present invention is that a solvent thermal reaction is carried out under aqueous solution conditions using an organic polyol mixed solvent and an oxygen vanadium precursor material as raw materials, and a near-layered organic hybrid vanadium oxide material embedded in a mixed molecule is successfully prepared under the condition that the volume ratio of the aqueous solution to the organic alcohol mixed solvent is 11 mL: 6 mL; the near-layered organic hybrid vanadium oxide material embedded in the mixed molecule is used as an electrode material for an energy storage device, and has an ordered-disordered mixed structure, which not only retains an ordered layered structure, but also exposes more active sites due to the disordered structure, thereby achieving faster ion diffusion. In addition, organic hybridization can reduce the electrostatic force between metal ions and the framework, and can also effectively expand the interlayer spacing, thereby constructing a more stable structure. In terms of electrochemical performance, it exhibits a high specific capacity, good rate capability and long-term cycle stability.
[0018] Comparison of specific capacity, rate capability and cycle stability with other typical vanadium-based cathode materials: . BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a scanning electron microscope image of a mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 2:1 as a raw material.
[0020] Figure 2 The scanning electron microscope images of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using ethylene glycol and propylene glycol mixed solvents with volume ratios of 6:0, 1:1, 1:2, and 0:6 as raw materials.
[0021] Figure 3 This is the XRD spectrum of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared by using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 6:0, 2:1, 1:1, 1:2, and 0:6 as the raw material in Example 1.
[0022] Figure 4 FT-IR spectra of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 6:0, 2:1, 1:1, 1:2, and 0:6 as the raw material.
[0023] Figure 5 This is a transmission electron micrograph of the near-layered organic hybrid vanadium oxide material in which the mixed molecules are embedded when the solvent thermal time is 36 h in Example 2.
[0024] Figure 6This is a high-resolution transmission electron microscopy image of the near-layered organic hybrid vanadium oxide material embedded with the mixed molecules obtained in Example 2 when the solvothermal time was 36 h.
[0025] Figure 7 The XRD spectra of the near-layered organic hybrid vanadium oxide material with mixed molecules embedded when the solvent thermal time is 24 h, 36 h, and 48 h in Example 2.
[0026] Figure 8 FT-IR spectra of the near-layered organic hybrid vanadium oxide material embedded with mixed molecules obtained in Example 2 using solvothermal times of 24 h, 36 h, and 48 h.
[0027] Fig. 9 This is a charge and discharge rate property diagram of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared as raw material using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 2:1 and a solvothermal time of 36 h in Example 1.
[0028] Fig.10 This is a constant current charge-discharge curve of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared as the raw material in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 2:1 and a solvothermal time of 36 h.
[0029] Fig.11 This is a long cycle property diagram of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared as raw material using a mixed solvent of ethylene glycol and propylene glycol with a volume ratio of 2:1 and a solvothermal time of 36 h in Example 1.
[0030] Fig.12 The cyclic voltammetry curve of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 2:1 and a solvothermal time of 36 h as the raw material. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1-12As shown, the preparation of a near-layered organic hybrid vanadium oxide material embedded with mixed molecules is characterized in that it includes the following steps: 1) adding a vanadium oxide precursor material to a solution obtained by fully stirring an aqueous solution and an organic polyol mixed solvent in a volume ratio of 11 mL:6 mL, and mixing again, the mixture is fully stirred at room temperature for 12 h to 48 h, preferably 12 h, to obtain a mixed solution; 2) performing a solvothermal reaction of the mixed solution in a stainless steel reactor, the inner lining of the stainless steel reactor is preferably a polytetrafluoroethylene material, the temperature of the solvothermal reaction is 180 ° C to 210 ° C, preferably 205 ° C; the insulation time is 24 h to 48 h, preferably 36 h; 3) after the solvothermal reaction is completed and naturally cooled, taking out the reaction liquid, repeatedly washing the precipitate obtained by centrifugal separation with ethanol until impurities are removed, and drying in an oven at a drying temperature of 60 ° C to 100 ° C, preferably 80 ° C; the time is 12 h to 48 h, preferably 24 h, to obtain the near-layered organic hybrid vanadium oxide material embedded with the mixed molecules.
[0032] The organic polyol mixed solvent includes one or both of ethylene glycol and glycerol.
[0033] The vanadium oxides include commercial V2O 5, Vanadates include NH4VO3.
[0034] The volume ratio of ethylene glycol to propylene glycol in the organic polyol mixed solvent is 1-4:2; preferably 2:1, 1:1, 1:2.
[0035] The molar mass ratio of the vanadium oxyhydroxide precursor material in the mixed solution is 0.1176 mol / L.
[0036] The mixed molecule embedded near-layered organic hybrid vanadium oxygen material contains vanadium, oxygen, carbon and hydrogen.
[0037] The near-layered organic hybrid vanadium oxide material in which the mixed molecules are embedded is a spherical structure of nanosheet stacking.
[0038] The mixed molecule embedded near-layered organic hybrid vanadium oxide material is used as an electrode material for energy storage devices.
[0039] The energy storage device is preferably an aqueous zinc ion battery, and the electrode material is preferably a positive electrode material.
[0040] The electrode material of the energy storage device includes a near-layered organic hybrid vanadium oxide material embedded with mixed molecules, a conductive agent and a binder; the mass ratio of the near-layered organic hybrid vanadium oxide material embedded with mixed molecules, the conductive agent and the binder is 7:2:1; the conductive agent is carbon black Super-p, and the binder is polyvinylidene fluoride PVDF.
[0041] The near-layered organic hybrid vanadium oxide material embedded with mixed molecules as the electrode material of the energy storage device has an ordered-disordered hybrid structure, which not only retains the ordered layered structure, but also exposes more active sites due to the disordered structure, thus achieving faster ion diffusion. In addition, the present invention can reduce the electrostatic force between metal ions and the framework through organic hybridization, and can also effectively expand the interlayer spacing, thereby constructing a more stable structure. In terms of electrochemical performance, it shows a high specific capacity, good rate capability and long-term cycle stability.
[0042] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with embodiments. Example 1
[0043] Mix 6 mL and 0 mL, 4 mL and 2 mL, 3 mL and 3 mL, 2 mL and 4 mL, and 0 mL and 6 mL of the mixed solvent of ethylene glycol and glycerol with 11 mL of the aqueous solution.
[0044] Add 0.234 g NH4VO3 to the 5 mixed solutions in step (1) and stir until completely mixed to form a uniform solution.
[0045] The five mixed solutions obtained in step (2) were added into the polytetrafluoroethylene liner of a 17 mL stainless steel reactor respectively, which was sealed and placed in an oven at a reaction temperature of 205 °C for 24 h to carry out a solvothermal reaction.
[0046] After the solvent thermal reaction was completed and cooled naturally, the reaction liquid was taken out, and the obtained precipitate was repeatedly washed with ethanol until the impurities were removed, and then dried in an oven at 80 °C for 24 h.
[0047] Figure 1 This is a scanning electron microscope image of a near-layered organic hybrid vanadium oxide material embedded with mixed molecules prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 2:1 as a raw material. Figure 2 a, b, c, d are scanning electron microscope images of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using the ethylene glycol propylene glycol mixed solvent volume ratio of 6: 0, 1: 1, 1: 2, 0: 6 as the raw material. Figure 1 and Figure 2 From a, b, c, and d, it can be seen that the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol with a volume ratio of 6:0, 2:1, 1:1, 1:2, and 0:6 as the raw material is a spherical structure with lamellar stacking.
[0048] Figure 3The XRD patterns of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 6:0, 2:1, 1:1, 1:2, 0:6 as the raw material. Figure 3 It can be seen that the organic hybrid vanadium oxide material prepared as raw material in Example 1 using a mixed solvent of ethylene glycol and glycerol in a volume ratio of 6:0 is in a crystalline state, and the organic hybrid vanadium oxide material prepared as raw material in Example 1 using a mixed solvent of ethylene glycol and glycerol in a volume ratio of 2:1, 1:1, 1:2, and 0:6 is an ordered-disordered mixed structure.
[0049] Figure 4 The FT-IR spectrum of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared in Example 1 using a mixed solvent of ethylene glycol and propylene glycol in a volume ratio of 6:0, 2:1, 1:1, 1:2, 0:6 as the raw material. Figure 4 It can be seen that the VOV bond strength of the mixed alcohol solvent is enhanced, and a more stable VO5 structure is constructed. At the same time, with the addition of propylene glycol in the mixed alcohol solvent, the change in the strength of the CH bond and the OH bond proves that both ethylene glycol and propylene glycol are indeed embedded between the sample layers, which is a near-layered organic hybrid vanadium oxide material embedded with mixed molecules. Example 2
[0050] Mix 4 mL and 2 mL of the mixed solvent of ethylene glycol and glycerol with 11 mL of the aqueous solution.
[0051] (2) Add 0.234 g NH4VO3 to the mixed solution in step (1) and stir until completely mixed to form a uniform solution.
[0052] (3) The mixed solution obtained in step (2) was added into the polytetrafluoroethylene liner of a 17 mL stainless steel reactor, which was sealed and placed in an oven at a reaction temperature of 205 °C for 36 h to carry out a solvothermal reaction.
[0053] (4) After the solvothermal reaction is completed and cooled naturally, the reaction liquid is taken out and the obtained precipitate is repeatedly washed with ethanol until the impurities are removed, and then dried in an oven at 80 °C for 24 h.
[0054] Figure 5 This is a transmission electron micrograph of the near-layered organic hybrid vanadium oxide material in which the mixed molecule is embedded when the solvothermal time is 36 hours in Example 2; Figure 6 The high-resolution transmission electron microscopy image of the near-layered organic hybrid vanadium oxide material embedded with the mixed molecule obtained in Example 2 when the solvothermal time is 36 h; Figure 5 and Figure 6It can be concluded that the nearly layered organic hybrid vanadium oxide material embedded in the mixed molecule obtained when the solvothermal time is 36 h is a lamellar stacking structure. Example 3
[0055] (1) Mix 4 mL and 2 mL of the mixed solvent of ethylene glycol and propylene glycol with 11 mL of the aqueous solution.
[0056] (2) Add 0.234 g NH4VO3 to the mixed solution in step (1) and stir until completely mixed to form a uniform solution.
[0057] (3) The mixed solution obtained in step (2) was added to the polytetrafluoroethylene liner of a 17 mL stainless steel reactor, which was sealed and placed in an oven at a reaction temperature of 205 °C for 24 h, 36 h, and 48 h to perform a solvothermal reaction. Figure 7 As shown in the figure, the organic hybrid vanadium oxide materials obtained with solvothermal time of 24 h, 36 h, and 48 h are all ordered-disordered mixed structures. Among them, the near-layered organic hybrid vanadium oxide material embedded with mixed molecules with a solvothermal time of 36 h has a stronger signal on the (111) crystal plane, proving that the sample is easier to grow along the c-axis and form a thinner sheet structure.
[0058] (4) After the solvothermal reaction is completed and cooled naturally, the reaction liquid is taken out and the obtained precipitate is repeatedly washed with ethanol until the impurities are removed, and then dried in an oven at 80 °C for 24 h.
[0059] Figure 8 The FT-IR spectra of the near-layered organic hybrid vanadium oxide material embedded with the mixed molecules obtained in Example 2 when the solvent thermal time is 24 h, 36 h, and 48 h; Figure 8 As shown, as the solvothermal time increases, the VO bond-related peak red-shifts, and the organic functional group (CH bond and OH bond) signal increases. This phenomenon is more obvious when the solvothermal time is 36 h. And when the solvothermal time is 24 h, 36 h, and 48 h, the organic ligand-related vibrations still exist in the near-layered organic hybrid vanadium oxide material embedded with the mixed molecule, which proves that the material prepared by the present invention is a near-layered organic hybrid vanadium oxide material embedded with the mixed molecule. Example 4
[0060] (1) Add the vanadium precursor material to the solution obtained by fully stirring the aqueous solution and the organic polyol mixed solvent in a volume ratio of 11 mL:6 mL, and then fully stir again at room temperature for 12 h to obtain a mixed solution; (2) performing a solvothermal reaction of the mixed solution in a stainless steel reactor, the inner lining of which is preferably made of polytetrafluoroethylene, the temperature of the solvothermal reaction being 180 °C, and the holding time being 24 h; (3) After the solvothermal reaction is completed and cooled naturally, the reaction liquid is taken out, and the precipitate obtained by centrifugal separation is repeatedly washed with ethanol until impurities are removed, and then dried in an oven at a temperature of 60°C for 12 h to obtain a near-layered organic hybrid vanadium oxide material embedded with the mixed molecule. Example 5
[0061] (1) Add the vanadyl precursor material to the solution obtained by fully stirring the aqueous solution and the organic polyol mixed solvent in a volume ratio of 11 mL:6 mL, and then fully stir again at room temperature for 48 h to obtain a mixed solution; (2) The mixed solution is subjected to a solvothermal reaction in a stainless steel reactor. The inner lining of the stainless steel reactor is preferably made of polytetrafluoroethylene. The temperature of the solvothermal reaction is 210 °C and the holding time is 48 h. (3) After the solvothermal reaction is completed and cooled naturally, the reaction liquid is taken out, and the precipitate obtained by centrifugal separation is repeatedly washed with ethanol until impurities are removed, and then dried in an oven at a temperature of 100 °C for 48 h to obtain a near-layered organic hybrid vanadium oxide material embedded with the mixed molecule. Application Example 1
[0062] 4 mL and 2 mL of a mixed solvent of ethylene glycol and glycerol were mixed evenly with 11 mL of an aqueous solution; 0.234 g NH4VO3 was added to the mixed solution and stirred until completely mixed to form a uniform solution, which was added to the polytetrafluoroethylene liner of a 17 mL stainless steel reactor, which was sealed and placed in an oven and maintained at a reaction temperature of 205 °C for 36 h for a solvothermal reaction; after the solvothermal reaction was completed and cooled naturally, the reaction liquid was taken out, and the obtained precipitate was repeatedly washed with ethanol until impurities were removed, and then dried in an oven at 80 °C for 24 h.
[0063] The mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared by taking the above-mentioned ethylene glycol-propylene glycol mixed solvent in a volume ratio of 2:1 as raw materials, carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1 are mixed evenly in N-methylpyrrolidone (NMP) to form a slurry, and then the slurry is evenly coated on a titanium mesh as a battery positive electrode, glass fiber is used as a separator, 3M Zn(CF3SO3)2 is used as an electrolyte, and the battery is packaged in a battery shell with a model CR2032 to prepare an aqueous zinc ion battery.
[0064] The electrochemical performance of the aqueous zinc ion battery prepared by the package was tested, such as Fig. 9 The constant current charge-discharge properties of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared by using a mixed solvent of ethylene glycol and propylene glycol with a volume ratio of 2:1 as the raw material solvent heat for 36 hours. Fig. 9 The near-layered organic hybrid vanadium oxide material embedded with mixed molecules has the characteristics of high specific capacity and high rate performance; Fig.10 As shown in the figure, the constant current charge-discharge curve of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared by using ethylene glycol propylene glycol mixed solvent with a volume ratio of 2:1 and a solvothermal time of 36 h as the raw material, as shown in the figure Fig.10 Shows high reversibility during charge and discharge; e.g. Fig.11 The long cycle properties of the mixed molecule embedded near-layered organic hybrid vanadium oxide material prepared by using a mixed solvent of ethylene glycol and propylene glycol with a volume ratio of 2:1 and a solvothermal time of 36 h as the raw material, wherein Fig.11 Figure a shows that the material is -1 After 1000 cycles at a current density of , the capacity retention rate is 94.9%. Fig.11 Figure b shows that the material is -1 Under high current density, the capacity retention rate is 82.4% during 5000 cycles, and both Figures a and b show good stability. Fig.12 The cyclic voltammetry curve of the mixed molecular embedded near-layered organic hybrid vanadium oxide material prepared by using ethylene glycol propylene glycol mixed solvent with a volume ratio of 2:1 and a solvothermal time of 36 h as the raw material is shown. Fig.12 The cyclic voltammetry curve of shows two pairs of redox peaks, indicating that there are multiple Zn 2+ The insertion and extraction behavior of the material is good, and the peak spacing of the redox peaks is very small, indicating that the material has high reversibility and small polarization.
Claims
1. Preparation of hybrid molecular embedded near-layered organic hybrid vanadium oxide materials, characterized by: The following steps are involved: 1) Add the vanadium oxide precursor material to the solution obtained by fully stirring the aqueous solution and the organic polyol mixed solvent in a volume ratio of 11 mL:6 mL, and then stir again, the stirring temperature is room temperature, the time is 12 h~48 h, preferably 12 h, to obtain a mixed solution; 2) The mixed solution is subjected to a solvothermal reaction in a stainless steel reactor, the lining of the stainless steel reactor is preferably polytetrafluoroethylene material, the temperature of the solvothermal reaction is 180 ℃~210 ℃, preferably 205 ℃; the insulation time is 24 h~48 h, preferably 36 h; 3) After the solvothermal reaction is completed and naturally cooled, the reaction liquid is taken out, the precipitate obtained by centrifugation is repeatedly washed with ethanol until impurities are removed, and dried in an oven, the drying temperature is 60 ℃~100 ℃, preferably 80 ℃; the time is 12 h~48 h, preferably 24 h, to obtain the near-layered organic hybrid vanadium oxide material embedded with the mixed molecule.
2. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1, characterized in that The organic polyol mixed solvent includes one or both of ethylene glycol and glycerol.
3. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1, characterized in that The volume ratio of ethylene glycol to propylene glycol in the organic polyol mixed solvent is 1-4:
2.
4. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1, characterized in that The vanadium oxide precursor material is vanadium oxide or vanadate, wherein the vanadium oxide includes commercial V2O5, and the vanadate includes NH4VO3.
5. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1, characterized in that The molar mass ratio of the vanadium oxyhydroxide precursor material in the mixed solution is 0.1176 mol / L.
6. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1, characterized in that The mixed molecule embedded near-layered organic hybrid vanadium oxygen material contains vanadium, oxygen, carbon and hydrogen.
7. The preparation of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 6, characterized in that The near-layered organic hybrid vanadium oxide material in which the mixed molecules are embedded is a spherical structure of nanosheet stacking.
8. Use of the mixed molecular embedded near-layered organic hybrid vanadium oxide material according to claim 1 in electrode materials for energy storage devices.
9. The use of the mixed molecular embedded near-layered organic hybrid vanadium oxide material in an electrode material of an energy storage device according to claim 8, characterized in that The energy storage device is an aqueous zinc ion battery, and the electrode material is preferably a positive electrode material.
10. The use of the mixed molecular embedded near-layered organic hybrid vanadium oxide material in an electrode material of an energy storage device according to claim 9, characterized in that The electrode material of the energy storage device includes a near-layered organic hybrid vanadium oxide material embedded with mixed molecules, a conductive agent and a binder; the mass ratio of the near-layered organic hybrid vanadium oxide material embedded with mixed molecules, the conductive agent and the binder is 7:2:1; the conductive agent is carbon black Super-p, and the binder is polyvinylidene fluoride PVD.
Citation Information
Patent Citations
Preparation method for sodium-ion battery cathode material Na3V2O2x(PO4)2F3-2x microspheres
CN105206831A
High-performance vanadium-based aqueous zinc ion battery and preparation method thereof
CN115207493A
Preparation method and application of small organic molecule intercalation vanadium pentoxide material
CN115360336A
Amorphous organic hybrid vanadyl material as well as preparation method and application thereof
CN117142520A
Layered vanadium-based material for regulating interlayer spacing by using solvent molecules / electrochemical active organic molecules as well as preparation method and application of layered vanadium-based material
CN118419976A